Interparental Conflict Across the Early Parenting Period: Evidence From Fathers Participating in an Australian Population-Based Study. (July 2022) - Giallo, Rebecca; Seymour, Monique; Treyvaud, Karli; Christensen, Daniel; Cook, Fallon; Feinberg, Mark; Brown, Stephanie; Cooklin, Amanda
Current evidence about the prevalence of interparental conflict (IPC) during early parenthood is primarily based on mothers' reports. Drawing upon Australian longitudinal data from 4136 fathers, the aims of the study were to: (a) report on the extent to which fathers report IPC across six biennial time intervals when their children were aged 6–12 months to 10–11 years, (b) identify trajectories of IPC over time and (c) identify postnatal factors (at the initial time point) associated with high risk trajectories of IPC. One in 10 fathers reported high IPC at each time interval. A high and increasing pattern of IPC was observed for 6% of fathers. Factors associated with this trajectory were fathers being from a non-English speaking background and high postnatal psychological distress reported by mothers and fathers. These findings underscore the importance of early intervention for some families experiencing IPC in the early years of their children's lives.